Aliovalent‐Ion‐Induced Lattice Regulation Based on Charge Balance Theory: Advanced Fluorophosphate Cathode for Sodium‐Ion Full Batteries. Issue 32 (2nd July 2021) - Gu, Zhen‐Yi; Guo, Jin‐Zhi; Sun, Zhong‐Hui; Zhao, Xin‐Xin; Wang, Xiao‐Tong; Liang, Hao‐Jie; Zhao, Bo; Li, Wen‐Hao; Pan, Xiu‐Mei; Wu, Xing‐Long
Abstract: There are still many problems that hinder the development of sodium‐ion batteries (SIBs), including poor rate performance, short‐term cycle lifespan, and inferior low‐temperature property. Herein, excellent Na‐storage performance in fluorophosphate (Na3 V2 (PO4 )2 F3 ) cathode is achieved by lattice regulation based on charge balance theory. Lattice regulation of aliovalent Mn 2+ for V 3+ increases both electronic conductivity and Na + ‐migration kinetics. Because of the maintaining of electrical neutrality in the material, aliovalent Mn 2+ ‐introduced leads to the coexistence of V 3+ and V 4+ from charge balance theory. It decreases the particle size and improves the structural stability, suppressing the large lattice distortion during cathode reaction processes. These multiple effects enhance the specific capacity (123.8 mAh g −1 ), outstanding high‐rate (68% capacity retention at 20 C), ultralong cycle (only 0.018% capacity attenuation per cycle over 1000 cycles at 1 C) and low‐temperature (96.5% capacity retention after 400 cycles at − 25 ° C) performances of Mn 2+ ‐induced Na3 V1.98 Mn0.02 (PO4 )2 F3 when used as cathode in SIBs. Importantly, a feasible sodium‐ion full battery is assembled, achieving outstanding rate capability and cycle stability. The strategy of aliovalent ion‐induced lattice regulation constructs cathode materials with superior performances, which is available to improve other electrode materials for energy storage systems. Abstract : An advanced Na3 V1.98 Mn0.02 (PO4 )2 F3 cathode with excellent energy‐storage performance is prepared via aliovalent substitution of V 3+ at Mn 2+ sites. It exhibits higher structural stability and improved electron/ion‐transport kinetics than pristine Na3 V2 (PO4 )2 F3 owing to aliovalent Mn 2+ induced lattice regulation based on charge balance theory leads to the coexistence of V 3+ / 4+, thereby extending the cycle life of NASICON cathode materials.